PELATIHAN TANGGAP BENCANA BERBASIS MODUL DAN SIMULASI TERHADAP PENGETAHUAN KESIAPSIAGAAN BENCANA - Iqra Iqra; Rusna Tahir (Politeknik Kesehatan Kemenkes Mamuju, 2022)
Indonesia as The Biggest Disaster Laboratory In The World has become a reference point for disaster management development by maximizing community empowerment independently, especially in disaster preparedness. Cognitive and psychic readiness for the community in the face of disasters can provide opportunities to decrease the impact of damage and casualties caused by the disaster. This research aims to determine the influence of module-based disaster response training and simulations on community preparedness knowledge in Konawe Regency. The design of this study uses quasy experiments with a pre post test with control group approach. The samples were grouped into two with the number of 30 respondents each in each group (intervention and control) selected by purposive sampling. The data was measured using questionnaires that had been tested for validity and reliability. The results of the statistical test using the Mann-Whitney test showed an increase in the preparedness knowledge of respondents after being given training using modules and simulations, where the average preparedness knowledge of the intervention group respondents was higher compared to the control group with a significance value of p = 0.001 (p<0.05). So it was concluded that module-based emergency response training and simulations affected preparedness knowledge.